Partisan power, economic coordination and variations in vocational training systems in Europe - Busemeyer, Marius R. [Verfasser]; Schlicht-Schmälzle, Raphaela [Verfasser] (My University, 2014)
"This article explores the variation of vocational education and training systems in European countries. From a survey of experts in 15 European countries, it develops a typology along two dimensions: employer involvement and public commitment. In a second step, it explains the variety of skill formation systems, highlighting the importance of partisan power and economic coordination. The causal argument is applied in three illustrative case studies of Germany, Sweden and the UK. In particular, the authors argue that a high degree of economic coordination increases the relevance of training relative to academic education and differences within the cluster of coordinated market economies are related to different legacies of partisan power in the post-war decades." (Author's abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 4.3 Steuerung; G 2.1.1 Ökonomie / Märkte; Berufsbildungssystem; Berufsausbildung; Bildungssteuerung; Korporatismus; Ordnungspolitik; Wirtschaftslenkung; Internationaler Vergleich; Europa